Czars in the White House : The Rise of Policy Czars as Presidential Management Tools - Vaughn, Justin S., 1978-; Villalobos, Jose D. (Book collections on Project MUSE., 2015)
When Barack Obama entered the White House, he faced numerous urgent issues. Despite the citizens' demand for strong presidential leadership, President Obama, following a long-standing precedent for the development and implementation of major policies, appointed administrators--so-called policy czars--charged with directing the response to the nation's most pressing crises. Combining public administration and political science approaches to the study of the American presidency and institutional politics, Justin S. Vaughn and Jose D. Villalobos argue that the creation of policy czars is a strategy for combating partisan polarization and navigating the federal government's complexity. They present a series of in-depth analyses of the appointment, role, and power of various czars: the energy czar in the mid-1970s, the drug czar in the late 1980s, the AIDS czar in the 1990s, George W. Bush's trio of national security czars after 9/11, and Obama's controversial czars for key domestic issues. Laying aside inflammatory political rhetoric, Vaughn and Villalobos offer a sober, empirical analysis of what precisely constitutes a czar, why Obama and his predecessors used czars, and what role they have played in the modern presidency.